Utilization of Different Fertilizer on The Yield of Two Varieties of Oryza sativa in Tidal Lowland Area - Neni Marlina; Dewi Meidelima; Asmawati Asmawati; Iin Siti Aminah (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
The effort to increase food production in tidal lowland areas was conducted by applying production technology through the use of superior varieties and organic fertilizer enriched with bacteria (bio organic fertilizer). This fertilizer was a formula that had been tested in swamp lowland area and proven capable to regain land fertility through action of beneficial microbia. Some microbia which used to produce bioorganic fertilizer are Azospirillium bacterium and phosphate solvent bacterium with carrier substance of chicken manure fertilizer. The reserach objective was to determine yield capacity of two rice varieties by using inorganic fertilizer and bioorganic fertilizer at tidal lowland area. This research was done at tidal lowland area of C-flooding type. The design used in this study was Factorial Randomized Block Design with 4 treatment combinations and 6 replications for each treatment. The first factor was varieties which consisted of Inpara 6 (V1) and Inpari I (V2), whereas the second factor was fertilizer types which consisted of inorganic fertilizer (P1) and bio-organic fertilizer (P2). The results showed that yield capacity of Inpari I rice variety treated with bio-organic fertilizer + 50% of recommended NPK fertilizer could increase the production of dry unhulled rice with magnitude of 165% (1.59 kg/plot or equal to 3.98 ton/ha) at tidal lowland of C flooding type. Through the provision of biofertilizers, chicken manure enriched with Azospirillum and bacteriophosphate biofertilizers contributes to sustainability agriculture, especially in tidal wetland